Application of Ceramsite Dust as an Active Pozzolan Additive in the Cement-Based Compositions. Issue 3 (November 2021) - Yakovlev, Grigory; Saidova, Zarina; Gordina, Anastasiya; Kuzmina, Natalia; Ginchitskaya, Yulia; Knyazeva, Svetlana; Elrefai, Ali Elsaed Mohamed Mohamed
Abstract: Ceramsite (expanded clay) dust is a waste material, obtained in large volumes all over the world as a by-product of ceramsite gravel production. With the development of the construction industry and the ever-growing amount of ceramsite dust disposed in the landfills, the recycling and rational use of this material is becoming a relevant issue. The currently available technologies for the ceramsite waste recycling are very limited, this is why it is necessary to develop a new effective way to involve this waste into the new production. The present research is based on the assumption that ceramsite dust can be applied effectively as an active pozzolanic mineral additive in the cement-based materials. In order to study the composition, structure and properties of the original clay used for the production of ceramsite, as well as the dehydrated clay dust, captured in the dust removing systems of kilns at ceramsite gravel plants, physical and chemical analysis methods were used. Based on the experimental data, the influence of ceramsite dust on the structure and properties of cement compositions was evaluated. Mechanical tests of the samples showed that the introduction of ceramsite dust as an additive in the amount of 3% by the cement weight leads to an increase in compressive strength by 23% in comparison with the reference composition. The paper also presents the results of microstructural analysis, IR spectral analysis and differential thermal analysis of samples modified with the optimal amount of this microadditive. The study of the microstructure of the modified samples shows that the introduction of ceramsite dust into the composition of the cement stone does not only change the morphology of new formations, thus increasing the density of the structure, but also varies the mineralogical composition of the cement matrix with the formation of stronger and more water-resistant minerals in the form of calcium silicate hydrates and calcium aluminosilicate hydrates. This technology allows the recycling of waste from the production of ceramsite stone, thus improving the environmental situation and contributing to the creation of a circular economy.